2024
DOI: 10.18063/ijb.v7i3.362
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Electrohydrodynamic Bioprinting of Pre-vascularized Cell-laden Constructs for Tissue Engineering

Abstract: Recapitulating the vascular networks that maintain the delivery of nutrition, oxygen, and byproducts for the living cells within the three-dimensional (3D) tissue constructs is a challenging issue in the tissue-engineering area. Here, a novel coaxial electrohydrodynamic (EHD) bioprinting strategy is presented to fabricate thick pre-vascularized cell-laden constructs. The alginate and collagen/calcium chloride solution were utilized as the outer-layer and inner-layer bioink, respectively, in the coaxial printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The self-assembly of cell/matrix mixtures under the guidance of micropatterned micropillars further allowed for the generation of aligned cellular architectures in simple tissue models 22 , 23 , but such hydrogel-based tissues failed to recapitulate the biomimetic mechanical and cellular heterogeneity (e.g., vascular components) in a controllable manner. Recent advances in the bioprinting of cell/hydrogel bioinks have provided opportunities to fabricate cellular constructs with CMs and embedded vascular structures as predesigned architectures 24 26 . Still, printing tissue constructs with the in vivo-like highly aligned and densely packed cellular arrangement, microscale hierarchical vascular structure, and sufficient mechanical property remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly of cell/matrix mixtures under the guidance of micropatterned micropillars further allowed for the generation of aligned cellular architectures in simple tissue models 22 , 23 , but such hydrogel-based tissues failed to recapitulate the biomimetic mechanical and cellular heterogeneity (e.g., vascular components) in a controllable manner. Recent advances in the bioprinting of cell/hydrogel bioinks have provided opportunities to fabricate cellular constructs with CMs and embedded vascular structures as predesigned architectures 24 26 . Still, printing tissue constructs with the in vivo-like highly aligned and densely packed cellular arrangement, microscale hierarchical vascular structure, and sufficient mechanical property remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…used coaxial electrohydrodynamic bioprinting (EHD) to create thick prevascularized cell‐laden constructs. [ 50 ] All these studies demonstrated the potential of bioprinting in vascular tissue engineering and the formation of complex vascular networks in 3D structures. Thriving toward more controlled complexity, heart‐on‐chip systems also appeared.…”
Section: Bioprinting Technologies On Earth and Their Applicability In...mentioning
confidence: 99%
“…Small diameter artificial blood vessels produced by coaxial printing exhibit excellent biocompatibility, cell proliferation, and cell differentiation. [33,34] Alg-based artificial blood vessels prepared by coaxial printing are not only fast and easy to prepare but also have a significant improvement in cells proliferation. However, the problem is lack of mechanical properties and anticoagulability.…”
Section: Morphologies and Permeabilitiesmentioning
confidence: 99%